Memory-Enhancing Activity of Palmatine in Mice Using Elevated Plus Maze and Morris Water Maze - Dinesh Dhingra; Varun Kumar (Advances in Pharmacological Sciences)
The present study was designed to evaluate the effect of palmatine on memory of Swiss young male albino mice. Palmatine (0.1, 0.5, 1 mg/kg, i.p.) and physostigmine (0.1 mg/kg, i.p.) per se were administered for 10 successive days to separate groups of mice. Effect of drugs on learning and memory of mice was evaluated using elevated plus maze and Morris water maze. Brain acetylcholinesterase activity was also estimated. Effect of palmatine on scopolamine- and diazepam-induced amnesia was also investigated. Palmatine (0.5 and 1 mg/kg) and physostigmine significantly improved learning and memory of mice, as indicated by decrease in transfer latency using elevated plus maze, and decrease in escape latency during training and increase in time spent in target quadrant during retrieval using Morris water maze. The drugs did not show any significant effect on locomotor activity of the mice. Memory-enhancing activity of palmatine (1 mg/kg) was comparable to physostigmine. Palmatine (1 mg/kg) significantly reversed scopolamine- and diazepam-induced amnesia in mice. Palmatine and physostigmine also significantly reduced brain acetylcholinesterase activity of mice. Thus, palmatine showed memory-enhancing activity in mice probably by inhibiting brain acetylcholinesterase activity, through involvement of GABA-benzodiazepine pathway, and due to its antioxidant activity.